Quantification and Comprehensive Analysis of Mesenchymal Stromal Cells in Bone Marrow Samples from Sickle Cell Disease Patients with Osteonecrosis - Tiago O. Ribeiro; Paula B. Daltro; Gildasio Cerqueira Daltro; Songeli M. Freire; Roberto Meyer; Vitor Fortuna (Stem Cells International)
The potential use of bone marrow mesenchymal stromal cells (BM-MSCs) for the treatment of osteonecrosis in sickle cell disease (SCD) patients is increasing. However, convenient BM-MSC quantification and functional property assays are critical factors for cell-based therapies yet to be optimized. This study was designed to quantify the MSC population in bone marrow (BM) samples from SCD patients with osteonecrosis (SCD group) and patients with osteoarticular complications not related to SCD (NS group), using flow cytometry for CD271+CD45-/low cell phenotype and CFU-F assay. We also compared expanded BM-MSC osteogenic differentiation, migration, and cytokine secretion potential between these groups. The mean total cell number, CFU-F count, and CD271+CD45-/low cells in BM mononuclear concentrate were significantly higher in SCD than in NS patients. A significant correlation between CD271+CD45-/low cell number and CFU-F counts was found in SCD (r=0.7483; p=0.0070) and NS (r=0.7167; p=0.0370) BM concentrates. An age-related quantitative reduction of CFU-F counts and CD271+CD45-/low cell number was noted. Furthermore, no significant differences in the morphology, replicative capacity, expression of surface markers, multidifferentiation potential, and secretion of cytokines were found in expanded BM-MSCs from SCD and NS groups after in vitro culturing. Collectively, this work provides important data for the suitable measurement and expansion of BM-MSC in support to advanced cell-based therapies for SCD patients with osteonecrosis.